Presenting an effective and easy method for designing and tuning predictive controller for boost and buck-boost converters in Continuous Conduction Mode. (September 2021) - Anzehaee, Mohammad Mousavi; Hajihosseini, Payman; Behnam, Behzad
Abstract: The main goal of this research is to introduce an easy algorithm for designing and tuning the model-based predictive controller in the A RMarkov-PFC P lus P ID (APP) controller to control boost converter, which has been previously presented by the authors of this paper. The proposed algorithm was more straightforward than the previous one and does not need the predictive model. Simulation results confirmed their performance was very close to each other. Meanwhile, APP controller – tuned by the new method – was used to control buck-boost converter in this research. Simulation and experimental results proved the efficiency of the new presented method. Highlights: A new tuning method is presented for ARMarkov-PFC in APP controller. An ARMarkov-PFC predictive controller is used to control buck boost converter. A hybrid controller of PID Type III​ and ARMarkov-PFC is introduced for buck boost converter.